2019
DOI: 10.1111/jfpe.13314
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dynamic quality changes and optimization of drying parameters of carrots (Daucus carota var. laguna)

Abstract: The effect of air temperature and sample thickness on the color changes and total carotenoids content of carrot slices was investigated. Temperature, exposure time, and moisture levels significantly affected the dynamic changes of total carotenoids and color. A slow and linear decrease in total carotenoids was observed at higher moisture content until reaching an inflection point at around 0.45 g w/ g dm for all temperatures studied . Thereafter, the retention in total carotenoids decreased rapidly. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 74 publications
(85 reference statements)
11
36
0
Order By: Relevance
“…Carotenoids degradation from 40% to 98.7% due to convective drying at 50–70 °C was reported in pumpkins [64] apricots [65] jackfruit bulb [66] . Considering carrot drying, [67] reported 17% degradation at 60 °C and 36% at 90 °C, while [12] reported degradation of 52.5% at 50 °C and 57.8% at 70 °C. However, convective drying conducted at 40 °C retained 92% of carrot carotenoids [68] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoids degradation from 40% to 98.7% due to convective drying at 50–70 °C was reported in pumpkins [64] apricots [65] jackfruit bulb [66] . Considering carrot drying, [67] reported 17% degradation at 60 °C and 36% at 90 °C, while [12] reported degradation of 52.5% at 50 °C and 57.8% at 70 °C. However, convective drying conducted at 40 °C retained 92% of carrot carotenoids [68] .…”
Section: Resultsmentioning
confidence: 99%
“…Convective drying was conducted in a tray dryer (UOP8MKII, Armfield®, England) at 40 °C with air velocity of 1 m/s. This temperature was selected in order to minimize carotenoid degradation, once a decrease of 52.5 and 57.8% were observed in the carotenoid content of dried carrots at 50 and 70 °C respectively [12] . The carrot slices were placed on perforated metal trays, allowing the hot air flows through all their surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Like strategy A, this strategy was also conducted for all three temperatures. As for the step-wise temperature-controlled strategies S50 and S40, the goal was to examine the effects of lowering the air temperature at the inflection point identified by Md Saleh et al (2019) on the colour and total carotenoid retention of the carrots. To this effect, the air temperature was held constant at 60°C until the inflection point (30% MC), which in this study was at 80 min and thereafter lowering the temperature by either 10°C (S50) or 20°C (S40).…”
Section: Dryermentioning
confidence: 99%
“…Hence, the authors call for an optimum intermittency level that allows balancing both the quality and energy aspects within the drying process. To this end, Md Saleh et al (2019) conducted drying experiments to identify the critical point on the nutritional degradation curve to improve the product quality and extending to process efficiency. The authors identified that for carrots, an inflection point at 30% moisture content was critical for total carotenoid retention as above this point the beta carotene loss decreased at a low rate and significantly increased below the inflection point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation